Economic Democracy and Unemployment in the Digital Age : A Sociolegal Study of Finland and Germany - Muchlis, Zaini; Saleh, Muhammad Aunurrahim Mas'ad; Permatasari, Niken Ayu; Maulana, M Roki; Harwanto, Aditya Putra (Pustaka Peradaban, 2024)
This article examines how Finland and Germany integrate the principles of economic democracy within their legal frameworks to address unemployment challenges in the digital era. Digitalisation and globalisation have intensified unemployment as a multidimensional issue, linked to justice, inclusiveness, and human rights. The study explores legal mechanisms employed by these nations to uphold economic democracy and mitigate unemployment. Finland’s universal welfare model prioritises inclusiveness through comprehensive social support, while Germany’s social market economy achieves a balance between market flexibility and contribution-based protections. Both countries tackle digital challenges, including automation and unequal access to technology, by strengthening labour rights, promoting workforce education and retraining, and enhancing social protections. This comparative legal analysis highlights how robust legal systems can address the socio-economic impacts of digitalisation and provide a model for inclusive economic policies.